Change in treatment coverage and barriers to mental health care among adults with depression and alcohol use disorder: a repeat cross sectional community survey in Nepal - Nagendra P. Luitel; Emily C. Garman; Mark J. D. Jordans; Crick Lund (BMC, 2019)
Abstract Background Despite the availability of evidence-based treatment, there is a substantial gap between the number of individuals in need of mental health care and those who receive treatment. The aim of this study was to assess changes in treatment coverage and barriers to mental health care among adults with depression and alcohol use disorder (AUD) before and after implementation of a district mental health care plan (MHCP) in Nepal. Methods The repeat population-based cross-sectional community survey was conducted with randomly selected adults in the baseline (N = 1983) and the follow-up (N = 1499) surveys, 3 years and 6 months apart. The Patient Health Questionnaire and Alcohol Use Disorder Identification Test were used to screen people with probable depression and AUD. Barriers to seeking mental health care were assessed by using a standardized tool, the Barriers to Care Evaluation Scale (BACE). Results The proportion of the participants receiving treatment for depression increased by 3.7 points (from 8.1% in the baseline to 11.8% in the follow-up) and for AUD by 5.2 points (from 5.1% in the baseline to 10.3% in the follow-up study), however, these changes were not statistically significant. There was no significant reduction in the overall BACE score in both unadjusted and adjusted models for both depression and AUD. The possible reasons for non-significant changes in treatment coverage and barriers to care could be that (i) the method of repeat population level surveys with a random sample was too distal to the intervention to be able to register a change and (ii) the study was underpowered to detect such changes. Conclusion The study found non-significant trends for improvements in treatment coverage and barriers to mental health care following implementation of the district mental health care plan. The key areas for improvement in the current strategy to improve treatment coverage and barriers to mental health care included change in the content of the existing community sensitization program, particularly for changing attitude and intention of people with mental illness for seeking care.